The effect of formal debt advice on financial management and knowledge: Insights from a new longitudinal study in Britain - Laura Fumagalli; Peter Lynn; Jair Mu\~noz-Bugarin (University of Essex, Institute for Social and Economic Research (ISER), 2021)
Using data from a new sample of over-indebted people living in Britain who have not sought debt advice in the previous six months, we estimate the effect of seeking formal debt advice. Our results suggest that there is a negative selection into formal debt advice: people who do seek debt advice are those who experience financial difficulties and struggle to keep up with bills and credit commitments. However, we find that formal debt advice is likely to mitigate, and possibly counteract, these difficulties. Our results suggest that formal debt advice increases the probability of adopting strategies to reduce spending and decreases the probability of being turned down for credit. Formal debt advice also increases knowledge and understanding of the steps needed to get out of debt, and ultimately leads to a better self-reported financial situation, well-being and even physical health.
Keywords: 330; Psychology; Information Networks; Survey Methodology; Debt: Indebtedness; Well Being; Health; Surveys; Finance